DEMATEL Method for Contradiction Network Analyzing - Liu Shang; Hu Ji; Cao Zhongliang; Guo Jianhua; Wang Zhongshuang (Jixie chuandong)
In the process of innovation design,the contradiction network are often constructed as more than one contradiction which interact each other emerge from analyzing step of initial problem situation.It is the key problem for innovation design that how to select important contradiction,root cause contradiction and core contradiction correctly from contradiction network.As the result of analyzing on contradiction interaction pattern and strategy of contradiction network decomposing,oriented graph is used to expressed the interaction between contradictions in the network of contradiction,and the equation to get the cause degree of contradiction to others is built,then the selecting method of important contradiction,root cause contradictions and core contradictions based on DEMATEL is proposed,which involves the calculation of the important weight,causes degree and centers degree of a contradiction.Finally,a case study of reversing winch is used to verify that the proposal method is correct.